2022
DOI: 10.1186/s12904-022-00944-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating patient- and caregiver-reported outcome measures into the daily care routines of specialised outpatient palliative care: a qualitative study (ELSAH) on feasibility, acceptability and appropriateness

Abstract: Background The use of patient-reported outcome measures (PROM) and caregiver-reported outcome measures can raise the patient centeredness of treatment and improve the quality of palliative care. Nevertheless, the everyday implementation of self-report in patients and caregivers is complex, and should be adapted for use in specific settings. We aimed to implement a set of outcome measures that included patient and caregiver self- and proxy-reported outcome measures in specialised outpatient pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…A study of the feasibility of paper-based PROMs in German specialised palliative home care identified health care professionals’ concerns about burdening patients in this way. 9 In contrast, our results suggest that the use of ePROMs could also serve as a facilitator as it allows patients to better understand and express the perception of their illness.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A study of the feasibility of paper-based PROMs in German specialised palliative home care identified health care professionals’ concerns about burdening patients in this way. 9 In contrast, our results suggest that the use of ePROMs could also serve as a facilitator as it allows patients to better understand and express the perception of their illness.…”
Section: Discussionmentioning
confidence: 55%
“…2123 Our results suggest that this could be overcome for the setting of palliative home care by family caregivers using ePROMs as proxies, as it is already recommended for the implementation of paper-based PROM use. 9…”
Section: Discussionmentioning
confidence: 99%
“…Patient reported outcome measures are increasingly used in traditional palliative day care, but the acceptability and feasibility of outcome measurement is less established in newer settings. [61]…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…For the self-report, the SOPC-team members included the items into the conversations. Because we found in a previous study that it needs tact to address sensitive topics, we did not arrange predefined time points for selfreport, but made the default to assess every topic when the information was collectible [26]. If a self-report was not possible, e.g.…”
Section: Relativesmentioning
confidence: 99%
“…We found that they should be used considerately in order to minimize the burden on patients and relatives, and ensure their administration was manageable. It was also important that participants understood that the measures were useful [26].…”
Section: Introductionmentioning
confidence: 99%